2021
DOI: 10.1039/d1ra03309c
|View full text |Cite
|
Sign up to set email alerts
|

A novel one-step synthesis of Ce/Mn/Fe mixed metal oxide nanocomposites for oxidative removal of hydrogen sulfide at room temperature

Abstract: In this study, CeO2/Fe2O3, CeO2/Mn2O3, and CeO2/Mn2O3/Fe2O3 nanocomposites were synthesized by the calcination of molten salt solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…However, no breakthrough experiment was conducted below 0.2 g. Since the material has a high density, loading adsorbent below 0.2 g led to a narrow bed length (since the tube diameter was 6 mm), which had a poor adsorbate-adsorbent interaction. The maximum adsorption capacity of 1.31 mmol g −1 achieved for the synthesized nanocomposite is similar to or higher than those reported for commercial ZnO (1.16 mmol g −1 ) 39 , CeO 2 -Mn 2 O 3 -Fe 2 O 3 (0.83 mmol g −1 ) 28 , Mn 2 O 3 -Fe 2 O 3 (0.35 mmol g −1 ) 27 , α-Fe 2 O 3 -Na 2 SO 4 (1.06 mmol g −1 ) 29 , and ZnFe 2 O 4 (0.05 mmol g −1 ) 40 in similar experimental conditions.
Figure 4 H 2 S breakthrough curves for ( a ) dry/wet adsorbents; ( b ) wet adsorbent at different flowrate; ( c ) adsorbent loading.
…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…However, no breakthrough experiment was conducted below 0.2 g. Since the material has a high density, loading adsorbent below 0.2 g led to a narrow bed length (since the tube diameter was 6 mm), which had a poor adsorbate-adsorbent interaction. The maximum adsorption capacity of 1.31 mmol g −1 achieved for the synthesized nanocomposite is similar to or higher than those reported for commercial ZnO (1.16 mmol g −1 ) 39 , CeO 2 -Mn 2 O 3 -Fe 2 O 3 (0.83 mmol g −1 ) 28 , Mn 2 O 3 -Fe 2 O 3 (0.35 mmol g −1 ) 27 , α-Fe 2 O 3 -Na 2 SO 4 (1.06 mmol g −1 ) 29 , and ZnFe 2 O 4 (0.05 mmol g −1 ) 40 in similar experimental conditions.
Figure 4 H 2 S breakthrough curves for ( a ) dry/wet adsorbents; ( b ) wet adsorbent at different flowrate; ( c ) adsorbent loading.
…”
Section: Resultssupporting
confidence: 77%
“…The nanocomposite possessed a BET surface area of 21.03 m 2 g −1 and a pore volume of 0.07 cm 3 g −1 . These values are higher than other nanocomposites like Mn 2 O 3 /Fe 2 O 3 (6.18 m 2 g −1 , 0.12 cm 3 g −1 ) 27 , CeO 2 /Mn 2 O 3 /Fe 2 O 3 (15.64 m 2 g −1 , 0.09 cm 3 g −1 ) 28 , and Fe 2 O 3 /Na 2 SO 4 (2.89 m 2 g −1 , 0.01 cm 3 g −1 ) 29 used for the same applications. The spectrum has a broad band centred at 621 cm −1 for the metal–oxygen stretching vibrations 30 , 31 .…”
Section: Resultsmentioning
confidence: 67%
“…One important thing to note here is that though the oxidation state variation is expected during these redox reactions, the proportional changes in the %Mn n+ ratio are not high. The possible reason for this is the role of adsorbed molecular O 2 , which could re-oxidize these low oxidation state Mn ions to a higher valency 36,59 . But, from the Mn 2p and Mn 3s analyses, it is confirmed that the Mn sites in NMO are the active sites for the adsorption and oxidation of acidic gas molecules.…”
Section: Experimental Conditionmentioning
confidence: 99%
“…[37] Usually poisoned oxide catalysts with sulfur can be regenerated by using high-temperature calcination in an oxygen atmosphere and impregnation with an ammonium hydroxide solution. [61][62][63] The carbon-based catalysts can be regenerated by using washing, thermal sublimation, and a combination of the two. [64] For example, half of carbon-based catalysts' desulfurization performance can be restored by using Soxhlet washing (hot water) and deionized water washing followed by drying.…”
Section: Selective Oxidationmentioning
confidence: 99%
“…The formed sulfur can be removed by different methods: solution washing, thermal sublimation or both two [37] . Usually poisoned oxide catalysts with sulfur can be regenerated by using high‐temperature calcination in an oxygen atmosphere and impregnation with an ammonium hydroxide solution [61–63] . The carbon‐based catalysts can be regenerated by using washing, thermal sublimation, and a combination of the two [64] .…”
Section: Overview Of H2s Reaction Mechanismmentioning
confidence: 99%